Teaching towards Democracy with Postmodern and Popular Culture Texts
VIII, 258 p.
Keywords: This edited volume supports implementation of a critical literacy of popular culture for new times. It explores popular and media texts that are meaningful to youth and their lives. It questions how these texts position youth as literate social practitioners. Based on theories of Critical and New Literacies that encourage questioning of social norms, the chapters challenge an audience of teachers, teacher educators, and literacy focused scholars in higher education to creatively integrate popular and media texts into their curriculum. Focal texts include science fiction, dystopian and other youth central novels, picture books that disrupt traditional narratives, graphic novels, video-games, other arts-based texts (film/novel hybrids) and even the lives of youth readers themselves as texts that offer rich possibilities for transformative literacy. Syllabi and concrete examples of classroom practices have been included by each chapter author.